VERIFIKASI DOSIS DI INTERFACE MASSA PADA SIMULASI STEREOTACTIC BODY RADIOTHERAPY (SBRT) KANKER PARU DENGAN TEKNIK PENCITRAAN FAST CT - Iin Hidayanti Wulansari; Yosi Sudarsi Asril; Laras Ati Nur Fatimah; Wahyu Edy Wibowo; Supriyanto A. Pawiro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Lung cancer is one of the cancer disease that most causes death in developing country. Dose prediction for lung cancer is difficult at radiotherapy because interface region in which treatment planning system (TPS) cannot calculate dose accuratelly. This error prediction can affect to lung cancer outcome, especially on SBRT which use high dose on single fraction. CIRS phantom with mass in left lung is used to simulate lung cancer that move with amplitude 0 mm, 5 mm, 10 mm, and 20 mm. The objective of this work is to verify dose at interface mass on lung cancer simulation to determine discrepancy between TPS Pinnacle3 dose calculation and measured dose using Gafchromic Film Gafchromic EBT3. The result showed that for static phantom, dose at interface mass was consitent with TPS doses. But, for dinamic phantom dose at interface significantly lower than TPS dose.Keywords: Lung-tumor interface, lung cancer, SBRT.